2001
DOI: 10.1021/es000275e
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of 4-Chloro-3-methylphenol in Pressurized Hot Water/Supercritical Water with Potassium Persulfate as Oxidant

Abstract: 4-Chloro-3-methylphenol (c = 2.0 mM), representing a model pollutant, was oxidized in pressurized hot water and in supercritical water in a continuous flow system. Potassium persulfate was used as oxidant in concentrations of 8.0 and 40.0 mM. Contact times (reaction times) were 3-59 s, temperatures 110-390 degrees C, and pressures 235-310 bar. A wide temperature range was tested to determine the range over which potassium persulfate can be used effectively. Good oxidation efficiencies for 4-chloro-3-methylphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…5 Physical activation such as UV irradiation or heating is able to effectively stimulate PS to produce sulfate radicals for oxidation of pollutants. [8][9][10] Chemical activation such as bases, phenols, and quinones were reported to be effective for activating PS for in situ chemical oxidation (ISCO). [11][12][13] Recent studies also applied electrochemical methods or electron donors (zero-valent iron or ferrous ion (II)) for PS activation.…”
Section: Introductionmentioning
confidence: 99%
“…5 Physical activation such as UV irradiation or heating is able to effectively stimulate PS to produce sulfate radicals for oxidation of pollutants. [8][9][10] Chemical activation such as bases, phenols, and quinones were reported to be effective for activating PS for in situ chemical oxidation (ISCO). [11][12][13] Recent studies also applied electrochemical methods or electron donors (zero-valent iron or ferrous ion (II)) for PS activation.…”
Section: Introductionmentioning
confidence: 99%
“…After activation, PS then becomes a strong oxidant (up to E ¼ 2.05 V), and therefore, interest is significant for activating PS in water treatment to degrade emerging contaminants under a broad spectrum of environmental conditions. Both physical activation like UV irradiation and heating (Kronholm et al, 2001;Yang et al, 2014) and chemical activation such as bases, phenols, and quinones have been reported to be effective for PS activation (Furman et al, 2010;Ahmad et al, 2013;Fang et al, 2013). The PS activation may occur either through generation of free radicals or by nonracial processes (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that chlorinated aliphatic compounds including lindane, dieldrin, tetrachloroethene and trichloroethene could be completely dechlorinated with subcritical water in 1 h at 150-300 °C [13]. In addition, the combination of subcritical water with oxidizing agents such as permanganate, O 2 and air, via so-called subcritical water oxidation (SCWO) can effectively oxidize organic compounds that are normally very difficult to oxidize [14,15]. Dadkhah and Akgerman [14] showed that more than 99.99% of PAHs could be removed from soil with the combination of extraction and oxidation with air and O 2 at 250 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Dadkhah and Akgerman [14] showed that more than 99.99% of PAHs could be removed from soil with the combination of extraction and oxidation with air and O 2 at 250 °C. Kronholm et al [15] reported that more than 99.9% of 4-chloro-3-methylphenol was oxidized by potassium persulfate within 1 min at 250-300 °C under 23.5-31.0 MPa. Under subcritical and supercritical conditions, PCBs were rapidly degraded with oxidants within minutes [16,17].…”
Section: Introductionmentioning
confidence: 99%